Crustáceos asociados a macroalgas en Bajo Pepito, Isla Mujeres, Caribe mexicano - Campos V ázquez, Concepción (Revista de Biología Tropical, 2000)
Crustaceans associated with macroalgae were col1ected for one year by scuba diving in Bajo Pepito, Isla Mujeres, mexican Caribbean. A total of 148 organisms were found: three orders, 11 families, 18 genera and 19 species in nine types of associations. The order with highest abundance was Isopoda (112), followed by Amphipoda (20) and Decapoda (16)